Determinan Pembiayaan Bermasalah Sektor Pertambangan Pada Perbankan Syariah - Prasetyo Ramadhan (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
The aim of this research is to analyze the determinant of mining’s non performing financing in short-term and long-term. This research used Vector Error Correction Model (VECM). The result shows that in short-term FDR, IPI at the fifth lag and Interest Rate at the second lag have a significantly positive effect to Mining’s Non Performing Financing. CAR, IPI at the first lag and Interest Rate at the first lag have a significantly negative effect to Mining’s Non Performing Financing. Inflation and World Oil Price have no significantly effect to Mining’s Non Performing Financing. Meanwhile, in long-term FDR, CAR, IPI, World Oil Price and Interest Rate have a significantly positive effect to Mining’s Non Performing Financing. Inflation has a significantly negative effect to Mining’s Non Performing Financing.